2023
DOI: 10.1145/3617367
|View full text |Cite
|
Sign up to set email alerts
|

“It’s Weird That it Knows What I Want”: Usability and Interactions with Copilot for Novice Programmers

James Prather,
Brent N. Reeves,
Paul Denny
et al.

Abstract: Recent developments in deep learning have resulted in code-generation models that produce source code from natural language and code-based prompts with high accuracy. This is likely to have profound effects in the classroom, where novices learning to code can now use free tools to automatically suggest solutions to programming exercises and assignments. However, little is currently known about how novices interact with these tools in practice. We present the first study that observes students at the introducto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(17 citation statements)
references
References 83 publications
2
15
0
Order By: Relevance
“…Over-reliance on AI generated outputs is a commonly cited concern within the education community, and several students commented on this aspect, including: "it is critical for students to learn the ability to write code independently rather than relying only on AI-generated answers" and "I feel like it is too tempting of a tool to use through the labs and not learn and develop these skills yourself". These concerns align with previous work that has looked into students' opinions on AI code generation [25].…”
Section: Resistance and Negative Feedbacksupporting
confidence: 83%
See 1 more Smart Citation
“…Over-reliance on AI generated outputs is a commonly cited concern within the education community, and several students commented on this aspect, including: "it is critical for students to learn the ability to write code independently rather than relying only on AI-generated answers" and "I feel like it is too tempting of a tool to use through the labs and not learn and develop these skills yourself". These concerns align with previous work that has looked into students' opinions on AI code generation [25].…”
Section: Resistance and Negative Feedbacksupporting
confidence: 83%
“…Other studies on the capabilities of LLMs have revealed impressive proficiency in dealing with object-oriented programming tasks [5], Parsons problems [26], and compiler error messages [17]. Many of these explorations also revealed that LLMs are not infallible and can produce solutions that do not align with best programming practice [5], struggle with longer and higher-level specifications [12], and cause students to become confused reading code that they did not write themselves [14,25]. Babe et al showed that LLMs can mislead students, causing them to believe that their own prompts are more (or less) effective than they are in reality [2].…”
Section: Related Workmentioning
confidence: 99%
“…Vaithilingam et al looked at very early usage of students using LLMs to code and found that students preferred using it, despite it not decreasing their overall task completion times [29]. The fact that it didn't make novices any faster at solving programming problems could be because students struggle to understand code that has been autogenerated for them, as found by Prather et al [23]. Kazemitabaar et al found that students will utilize it to either explore new ways of doing a task or to attempt to accelerate their task completion time [10].…”
Section: Related Workmentioning
confidence: 99%
“…Researchers have been quick to measure the ability of these LLMs with regard to typical computer science programs [7,8], code explanations [12], exams [17], and even Parsons Problems (mixed-up code problems) [24]. This has led to instructors having many concerns, such as students using autogenerated code that they don't understand [23] or using these tools to do their work for them [1,11]. Still other concerns, such as over-reliance, biases inherent in the models, and trustworthiness, remain active points of discussion in current research [31].…”
Section: Introductionmentioning
confidence: 99%
“…Future research is also needed to evaluate the impact of proactive problem identification and assistance, focusing on the design of minimally distracting assistants. Indeed, recent work by Prather et al revealed that students did not like being shown suggestions when they felt they did not need the help [51].…”
Section: D2: Designing the Ai Querying Interfacementioning
confidence: 99%